The Impact of Community Empowerment in Self-Management Education on Medication Adherence Among Hypertension Patients: A Systematic Review - Windariyanti, Nunuk; Sri Rejeki, Dwi Sarwani; Wijayanti, Siwi Pratama Mars (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2026)
Hypertension, a chronic disease, remains a leading cause of global illness and death. Medication adherence is critical for managing hypertension, yet poor adherence is common. This systematic review evaluated how community empowerment and self-management education influence medication adherence in adults with hypertension. Using PRISMA guidelines, the review identified studies published in English from 2015 to 2025 in Google Scholar, PubMed, and Scopus, focusing on adult hypertensive populations and reporting adherence outcomes. Studies without educational or empowerment interventions were excluded. Two reviewers independently selected and assessed the quality of studies. Of 443 articles, six met the criteria. Results showed that structured self-management education, especially with personalized support and follow-up, significantly improved medication adherence. Community empowerment strategies, including family involvement, peer support, and engagement with local health workers, further enhanced motivation and long-term adherence. These findings highlight the importance of integrating self-management and community-based interventions into hypertension care. Such approaches may strengthen public health programs, promote sustained treatment adherence, and reduce hypertension-related complications. The review’s evidence supports prioritizing these strategies for better health outcomes. This review was not prospectively registered.